2008
DOI: 10.1007/978-3-540-92182-0_49
|View full text |Cite
|
Sign up to set email alerts
|

Preprocessing Imprecise Points and Splitting Triangulations

Abstract: Traditional algorithms in computational geometry assume that the input points are given precisely. In practice, data is usually imprecise, but information about the imprecision is often available. In this context, we investigate what the value of this information is. We show here how to preprocess a set of disjoint regions in the plane of total complexity n in O(n log n) time so that if one point per set is specified with precise coordinates, a triangulation of the points can be computed in linear time. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The framework for preprocessing regions that represent points was first introduced by Held and Mitchell [12], who show how to store a set of disjoint unit disks in a data structure such that any point set containing one point from each disk can be triangulated in linear time. This result was later extended to arbitrary disjoint regions in the plane by van Kreveld et al [17]. Löffler and Snoeyink first showed that the Delaunay triangulation (or its dual, the Voronoi diagram) can also be computed in linear time after preprocessing a set of disjoint unit disks [18].…”
Section: Related Workmentioning
confidence: 99%
“…The framework for preprocessing regions that represent points was first introduced by Held and Mitchell [12], who show how to store a set of disjoint unit disks in a data structure such that any point set containing one point from each disk can be triangulated in linear time. This result was later extended to arbitrary disjoint regions in the plane by van Kreveld et al [17]. Löffler and Snoeyink first showed that the Delaunay triangulation (or its dual, the Voronoi diagram) can also be computed in linear time after preprocessing a set of disjoint unit disks [18].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, we mention the paradigm of preprocessing imprecise points [7,17,20,22,24]. Given a set R of planar regions, we must preprocess R to quickly find the (Delaunay) triangulation or convex hull for inputs with exactly one point from each region in R. If we consider inputs with a random point from each region, the self-improving setting applies, and the previous results bound the expected running time in the limiting phase.…”
Section: Main Theoremsmentioning
confidence: 99%
“…Löffler and Snoeyink [22] were the first to interpret R as a collection of imprecise measurements of a true point set P . The size of Ξ and the running time of the reconstruction phase, together quantify the information about (the Delaunay triangulation of) P contained in R. This interpretation was widely adopted within computational geometry and motivated many recent results for constructing Delaunay triangulations [4,5,11,28], spanning trees [20,30], convex hulls [15,16,23,25] and other planar decompositions [21,27] for imprecise points.…”
Section: Introductionmentioning
confidence: 99%